2006
DOI: 10.1598/rt.59.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Invitations to Families in an Early Literacy Support Program

Abstract: Teachers know that when families are involved meaningfully in schools, students perform better in academic, behavioral, and emotional domains. This article describes a project designed to enhance the quality of children's literacy interactions with family members and simultaneously increase family involvement at school. The level of participation of a classroom teacher is key in implementing a family literacy support program in a low‐income neighborhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…This study found that family literacy programs are efficacious in improving family and child reading and literacy practices as other previous studies have shown [8,17,20,21,31,42]. The current study took a step further to investigate the role of different durations of the program and family characteristics.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…This study found that family literacy programs are efficacious in improving family and child reading and literacy practices as other previous studies have shown [8,17,20,21,31,42]. The current study took a step further to investigate the role of different durations of the program and family characteristics.…”
Section: Discussionsupporting
confidence: 51%
“…There is a connection between family involvement (or lack of involvement) and the development of early language and literacy skills and future success in school [8,9]. A mother's literacy level is a significant predictor of a child's future success in school and adults with lower literacy skills are less likely to read to their children [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the program enabled parents to help their children with school activities and increased parents' confidence in their own reading abilities. Waldbart, Meyers, and Meyers's (2006) Bridges to Literacy program fosters the reading development of poor children by forging a connection between schools and poor families. The Bridges to Literacy project works to increase parent-child literacy interactions and to promote schoolfamily collaboration in reading development.…”
Section: Parents As Partners In Readingmentioning
confidence: 99%
“…Unfortunately, as previously mentioned, many do not see the importance nor honor the literacy learning that is present in minority low-income homes (Waldbart et al, 2006). …”
Section: Literacy Learning and Funds Of Knowledge Theorymentioning
confidence: 99%